Ethical banking behavior among millennials and Gen-Z in Malaysia - Zahari, Siti Aisyah; Shahimi, Shahida; Alma'amun, Suhaili; Arshad, Mohd Mursyid (Emerald Publishing, 2024)
Purpose: This study aims to determine the factors that influence ethical banking behavior among millennials and Gen-Z in Malaysia. Design/methodology/approach: A stratified sample of 525 millennials and Gen-Z of Malaysian banking customers was used. Extended ethical decision-making (EDM) model was tested using partial least square-structural equation model for the analysis. Findings: The findings indicated that the engagement of millennials and Gen-Z in ethical banking is influenced by factors such as intention, judgment and awareness, which shaped both generations’ ethical banking behavior. Practical implications: This study could be a central reference point and assist banking institutions in understanding the preferences of millennials and Gen-Z. Originality/value: This study extends the previous EDM model that focused solely on consumer's belief systems. Three aspects differentiate this paper and contribute to its originality, namely, the uniqueness of millennials and Gen-Z behavior, incorporating new variables along with the EDM models and study in Malaysian context. © 2023, Siti Aisyah Binti Zahari, Shahida Shahimi, Suhaili Alma'amun and Mohd Mursyid Arshad.